SERUM CYSTATIN C AND MICROALBUMIN IN THE DETECTION OF EARLY NEPHROPATHY IN TYPE II DIABETIC PATIENTS. - SANGEETHA DAYANIDHI; K.RAMADEVI; I. PERIYANDAVAR (International Journal of Pharma and Bio Sciences, 2015)
Early identification of impairment in renal function is crucial in diabetic patients. The aim of this study was to assess serum Cystatin C and Albumin Creatinine Ratio (ACR) in type II Diabetic patients. 50 diabetic patients of age 40-75years were included in this study. Fasting blood samples and morning urine samples were collected for analysis of glucose, urea, cystatin C, creatinine and microalbumin respectively. Statistical analysis was done using Medcalc. Patients were categorized into normoalbuminuric and microalbuminuric based on Albumin Creatinine Ratio (ACR). Cystatin C increased with increasing degree of microalbuminuria and correlated with ACR in the age group 40- 49 and 50-59. The level of Cystatin C was found to be higher in patients with GFR ≤ 60ml/min/1.732m2 and hence Cystatin C is a predictor of early renal damage in patients even before the appearance of microalbuminuria. Therefore the determination of serum Cystatin C together with quantification of urinary microalbumin in patients with renal risk can optimize the early detection of renal damage.